A History of the Welsh English Dialect in Fiction - Benjamin A. Jones (2018)
The systematic study of language varieties in fictional texts have primarily focused upon written material. Recently, linguists have also added audio-visual genres to the analytic framework of literary dialect studies. Studies have traditionally examined writers’ lexical, phonological, and grammatical output; contemporarily, research has begun examining metalinguistic commentaries and linguistic indexing of character stereotypes to this repertoire (Hodson, 2014).Except for minor analysis of early texts (German, 2009), there has been no large-scale investigation of any Welsh English dialect in fiction. This thesis addresses this gap, asking the fundamental question: throughout history, how has Welsh English been represented in fiction? The thesis surveys a large chronological scope covering material from the 12th century until the present day across four narrative-genres: early writings and theatrical writing, novels, films, and, new to literary dialect studies, videogames. In doing so, a historical discussion forms that covers Welsh English’s fictolinguistic output, cross-referencing its linguistic forms with recorded data, identifying forms hitherto unknown to dialectological surveys, and addressing metalinguistic and attitudinal stereotypes in fiction.Key findings include that phonology was an early representational linguistic domain in the literary dialect, whilst lexical and grammatical domains became common from 19th century literature onwards. The commonest phonological and lexical features were glottal fricative drops and tapped /r/; and the endearment terms ‘bach/fach’ and ‘mam’ respectively. Grammatically, ‘Focus Fronting’ and ‘Demonstrative There’ regularly occurred. Regarding linguistic evidence, several authors and filmmakers were prolific lay surveyors of the variety, adding to the historical dialectological record. Concerning dialectal attitudes, Elizabethan playwrights used linguistic stereotyping to create character stereotypes of Welsh people as ‘comical’. By the 19th century, fictive Welsh English representation was the dominion of native-users in literature, film, and videogames; however today, the Comic stereotype, and an emerging stereotype of Welsh English users being Fantastical, appears embedded within the dialect’s representation.